Modeling hydration kinetics based on boundary nucleation and space-filling growth in a fixed confined zone. (May 2016) - Honorio, Tulio; Bary, Benoit; Benboudjema, Farid; Poyet, Stéphane
Abstract: A semi-analytical model of hydration kinetics based on the boundary nucleation and space-filling growth for early hydration and a diffusion-controlled kinetics for late hydration is proposed. The objective is to develop a simple model that can be coupled with more complex approaches required for the estimation of properties at early-age, but without neglecting some key mechanisms driving the kinetics. The particle size distribution (PSD) of cement is explicitly accounted for. The impingements are modeled by means of an exponential boundary condition in which a limited reaction zone is defined. Numerical solutions for the model are obtained and compared to experimental data. The model can reproduce some relevant features regarding hydration kinetics such as calorimetric data and the influence of the w/c ratio on late kinetics.